DAMPAK BUDAYA ORGANISASI TERHADAP EFEKTIVITAS KOMUNIKASI INTERNAL DI SEKOLAH MIS NURUL FADHILAH - Syahputra, Muhammad Rizki; Munawwarah, Tarisa; Sani, Dinda Aulia; Kholizah, Nur Alfiana; Siregar, Nur Khofifah (STKIP Pesisir Selatan, 2024)
Internal school communication includes various elements between students and teachers, teachers and students, teachers and students' parents and teachers and members of the school environment. Research The method used was an interview with one of the respondents, namely the MIS school teacher at Nurul Fadhilah. The method used in this research is qualitative research with a literature study approach. Research findings show that associations have an impact on the continuity of interior correspondence at the Nurul Fadhilah MIS School. The following were found to be the impacts of organizational culture: increasing employee engagement at work, job satisfaction, and motivation at work expanding the continuity of inner correspondence between leaders between organizational members and subordinates. The findings of this research indicate that an effective organization can be one that has a strong and positive communication culture, thereby improving the performance and efficiency of representatives. As a result, this research helps develop strategies. Effective communication in the MIS Nurul Fadhilah organization and other schools. The aim of this research is to find out how organizational culture influences the effectiveness of internal communication at the Nurul Fadhilah MIS School.